2021
DOI: 10.3390/ijerph18052585
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Skin Cultivable Microbiota Composition of the Frog Pelophylax perezi Inhabiting Different Environments

Abstract: Microorganisms that live in association with amphibian skin can play important roles in protecting their host. Within the scenarios of global change, it is important to understand how environmental disturbances, namely, metal pollution, can affect this microbiota. The aim of this study is to recognize core bacteria in the skin cultivable microbiota of the Perez frog (Pelophylax perezi) that are preserved regardless of the environmental conditions in which the frogs live. The characterization of these isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 66 publications
(55 reference statements)
1
3
0
Order By: Relevance
“…Enterobacteriaceae was the most abundant cultivable family identi ed in all skin samples of wild M. admirabilis. This result is in concordance with Proença et al, [20] that also showed Enterobacteriaceae was the most dominant cultivable family in skin samples of Perez's frogs (Pelophylax perezi) living in non-contaminated and contaminated rivers from Portugal. Besides, Bacillaceae, Moraxellaceae, and Aeromonadaceae were also observed in Perez's and Panamanian frogs [20,21].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Enterobacteriaceae was the most abundant cultivable family identi ed in all skin samples of wild M. admirabilis. This result is in concordance with Proença et al, [20] that also showed Enterobacteriaceae was the most dominant cultivable family in skin samples of Perez's frogs (Pelophylax perezi) living in non-contaminated and contaminated rivers from Portugal. Besides, Bacillaceae, Moraxellaceae, and Aeromonadaceae were also observed in Perez's and Panamanian frogs [20,21].…”
supporting
confidence: 92%
“…Bacillus sp., Citrobacter freundii, Janthinobacterium lividum, Pseudomonas sp., Serratia sp. found on amphibian's skin already showed inhibitory activity against Bd fungus [20,24,[33][34][35][36][37][38]. In addition, several bacteria of the amphibian skin act as component of the innate immune system of amphibians, acting as a barrier to pathogen infection and maintaining the species in an environment modulated by anthropic action [20,38].…”
mentioning
confidence: 99%
“…Adverse environmental changes resulting from human activities can cause changes in the symbiotic microbial community that can make the host more susceptible to pathogens [34]. Moreover, dysbiosis of the amphibian skin microbiota increases the sensitivity to pathogen infection and decreases skin defense and immune function [35,36]. For example, because integrated pig-fish farming causes pollution in ponds, the high concentration of fecal coliform bacteria in ponds largely reduces the diversity of the anurans skin microbiota, leading to a high proportion of Bd-facilitative bacteria in the skin microbiota and increasing the prevalence of Bd in the frogs [37].…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the impact of habitats disturbed by human activity on changes in the host skin microbiota is important for understanding how host-associated symbiotic microbial communities respond to changes in adverse environmental conditions [1]. Information on the skin microbiota of animals can both clarify the relationship between the skin microbiota composition and environmental factors [36] and provide a research basis for future provisioned populations. We studied the skin microbiota of Maoershan hynobiids using 16S rRNA high-throughput sequencing.…”
Section: Introductionmentioning
confidence: 99%